ROUGH FUZZY (FUZZY ROUGH) STRONG h-IDEALS OF HEMIRINGS - Zhan, Jianming; Liu, Qi; Kim, hee Sik (Italian Journal of Pure and Applied Mathematics, 2015)
By means of Dubois and Prade's idea, we apply rough fuzzy sets and fuzzy rough sets to algebraic structures. The concepts of rough fuzzy strong h-ideals (rough fuzzy prime ideals) and fuzzy rough strong h-ideals (fuzzy rough prime ideals) of hemirings are introduced, respectively. The relationships between them are investigated. Some characterizations of these two kinds of rough set theory of hemirings are explored.